5.5k views
2 votes
How do you solve for m? I'm having some trouble. Thank you for your help. (m-5)(m-1)=-3​

User Pleluron
by
4.9k points

1 Answer

0 votes

Using Distributive Property:

Combine and get all the terms in left sides and set it equal to zero and solve for m.

(m-5) (m-1) = -3 //Basic step of distribution.

m(m-1) -5(m-1) = -3

m^2 - m - 5m + 5 = -3 //Combine like terms and add 3 on both sides.

m^2 - 6m + 8 = 0 //Factor

m^2 - 4m - 2m + 8 = 0

m(m-4) -2(m -4) = 0

(m-4)(m-2) = 0 //Solve for m.

Got two equations:

1)m - 4 = 0

m = 4

2) m - 2 = 0

m = 2

Solution: m = 4, 2

//Hope this helps

User Vanity
by
4.9k points